2020
DOI: 10.1021/acs.iecr.0c00668
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption–Desorption Properties of Granular EP/HMO Composite and Its Application in Lithium Recovery from Brine

Abstract: The forming of adsorbent powder is the bottleneck of the current technology for lithium adsorption from brine. In this study, an epoxy resin (E-12) was directly adopted to prepare a cylindrical granular adsorbent (the EP/HMO composite) with excellent adsorption performance. Furthermore, the conventional adsorption–desorption process was optimized to improve the adsorptive efficiency for lithium. The batch experimental results showed that the adsorptive capacity for lithium per gram of granular adsorbents was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The high selectivity for Li + is rationalized with the ion sieve effect of the HMO: the spinel structure size is suitable for Li + , and suitable ion exchange occurs between H + and Li + . According to this rationalization, other metal ions can only be adsorbed on the surface by van der Waals force because their ionic radius is larger than the adsorption site/cavity size and/or because the free energy of hydration is larger than Li + , which prevents their entry into the HMO cavity site. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high selectivity for Li + is rationalized with the ion sieve effect of the HMO: the spinel structure size is suitable for Li + , and suitable ion exchange occurs between H + and Li + . According to this rationalization, other metal ions can only be adsorbed on the surface by van der Waals force because their ionic radius is larger than the adsorption site/cavity size and/or because the free energy of hydration is larger than Li + , which prevents their entry into the HMO cavity site. , …”
Section: Resultsmentioning
confidence: 99%
“…According to this rationalization, other metal ions can only be adsorbed on the surface by van der Waals force because their ionic radius is larger than the adsorption site/cavity size and/or because the free energy of hydration is larger than Li + , which prevents their entry into the HMO cavity site. 52,53 Results of Lithium Extraction and Recovery in Preliminary Depth Filtration Experiments. The emptybed contact time (EBCT) is an important parameter related to the reactor volume size or to the flow rate processable in a system and should be as small as possible to ensure the economy of the process.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For the adsorption method, the selection of adsorbents is very important. , Three kinds of adsorbents are reported frequently for lithium recovery from brines, including aluminum salt adsorbents, manganese-type lithium-ion sieves (HMO) and titanium-type lithium-ion sieves (HTO). Compared with aluminum salt adsorbents, lithium-ion sieves have obviously higher Li + adsorption capacities for the low-grade lithium recovery from brines, for example, actually achieving ∼40 mg (Li + )/g adsorption capacity on H 1.6 Mn 1.6 O 4 ion sieves, ∼30 mg (Li + )/g adsorption capacity on H 2 TiO 3 ion sieves. In our laboratory, we have prepared titanium-type lithium-ion sieves (PVB-HTO granules), and it is found that the home-made PVB-HTO granules have good cycling stability for the repetitive experiments of lithium adsorption and acid desorption. , Therefore, we use the home-made PVB-HTO granules to recover lithium from brines in this article.…”
Section: Introductionmentioning
confidence: 99%
“…10 Polymeric resin have been well-developed for wide application for water purification, metal ion adsorption and medical waste treatment, and so forth. [11][12][13][14][15][16][17] Although the crown ethers have been recognized as excellent binding units for alkali metal ion, its toxicity and high costs prevent direct modification on the polymeric resin to enhance the adsorption performance. [18][19][20][21][22][23][24][25][26][27] Therefore, to develop highly efficient polymeric resin showing satisfactory lithium adsorption capacity, low cost and good recycling abilities in the LIB industrial wastewater still pose great challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Their adsorption capacities are not satisfactory with the capacity less than 7 mg/L 10 . Polymeric resin have been well‐developed for wide application for water purification, metal ion adsorption and medical waste treatment, and so forth 11–17 . Although the crown ethers have been recognized as excellent binding units for alkali metal ion, its toxicity and high costs prevent direct modification on the polymeric resin to enhance the adsorption performance 18–27 .…”
Section: Introductionmentioning
confidence: 99%